PERAN AUSTRALIA DALAM BIDANG PENDIDIKAN UNTUK MENDUKUNG KEBIJAKAN MIGRATION WITH DIGNITY OLEH PEMERINTAHAN KIRIBATI (2006-2014) - Lady Chintia Nasution; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This Research describes Australia’s role in the education field to support the Migration With Dignity Policy by the Kiribati Government (2006-2014). Kiribati is a small country that is experiencing problem of the poverty, unemployment and sea level rise. It has been predicted that the islands of Kiribati will not inhabitable anymore in 30 years from now. The I-Kiribati have to migrate to another country before Kiribati islands uninhabitable. The government of Kiribati has announced a policy called “ Migration With Dignity” to prepare the migration of I-Kiribati. Australia help Kiribati by granting a scholarship program to I-Kiribati which allows them study nurse in Australia. This Research is concerned with how the KANI’s program could help prepare I-Kiribati migrate by using National Interest concept. This research used qualitative methods which is done by explaining the case based on existing facts. The techniques used to collects data to study the case to library research in the form of journals, books, official documents, report, magazine, paper, and website. The theoretical framework applied in this research are realism perspective, national interest concept, nation-state analysis level and foreign policy theory from Rosenau. KANI is a scholarship program offered Australia to Kiribati in the field of nursing education at Griffith Universty. This programs help Kiribati in addressing the issue of unemployment and poverty. The KANI participant have graduated and got a job in Autralia will acquire the status of permanent resident.Keywords: KANI, Migration With Dignity, Sea Level Rise, Foreign Policy